THE IMPACT OF WORKING CAPITAL MANAGEMENT AND COVID-19 ON THE PROFITABILITY OF COMPANIES IN INDONESIA - Ayuningtias, Kartika Sekar; Liza Handoko (Universitas Pelita Harapan, 2025)
This research examines the impact of working capital management and the COVID-19 pandemic on the profitability of Indonesian companies listed on the Indonesia Stock Exchange from 2013 to 2022, excluding financial firms. Using panel regression with a fixed effects model, the findings reveal that cash conversion cycle management and firm size significantly influence profitability, both in terms of ROA and ROE. Efficient cash conversion cycle management enhances profitability by reducing the time needed to convert inventory investments into cash, while larger firms benefit from economies of scale and greater market access. Additionally, accounts receivable management, current ratio, and leverage significantly affect ROA, whereas inventory management, current assets, and the COVID-19 pandemic show no significant impact. For ROE, only cash conversion cycle and firm size have a significant influence. These results highlight the importance of effective working capital management strategies to enhance corporate profitability.